Evaluación del hongo nematófago pochonia chlamydosporia, en el control del nemátodo del nudo Meloidogyne sp, en el cultivo de sacha Inchi Plukenetia Volubilis bajo condiciones de vivero - Leiva Piedra, Jorge Luis (2009)
The present work, aimed to control alternative to root knot nematode Meloidogyne incognita., cultivation modern uses, by using the nematofago Pochonia chlamydosporia fungus, which was evaluated for its effect, dosage, mode of application and control rate, so it identify the species of the genus Meloidogyne affecting crop modern uses in the San Martín region. For identification of the species, we used the models obtained from the female perineal nematode extracted from nodulated roots modern uses, come to identify the species M. incognita. To evaluate the effect of the fungus were worked with 6 treatments and a control, being used three doses (10g., 20g. and 30 g per kg. of soil) and two modes of application (in suspension and substrate rice) for all the sterilized soil treatments were used, which was placed in bags seedbeds 3 kilos, and in which a seed was planted modern uses, to then be infested with 400 eggs of M. incognita / 100 cc of soil. Two evaluations were made at 25 and 40 days after soil infestation. As the treatment 6 (30 g in suspension of the fungus per kg. of soil), which showed better results in both evaluations, with an index of nodulation of 16 and 13.3 nodules per plant, root weight increased with 19, 3 and 32 g. / Plant, plant height increased with 29 and 59 cm. respectively, compared to other treatments. Also observed in figures 14 and 15 that the control rate of P. chlamydosporia. showing growing in the 1st assessment in the control treatment 6 of 74, 25% and in the 2nd assessment control 86.87% respectively, showing us that the biological agent over time becomes established in the soil by increasing its share control.